Effects of laser scanning speeds on ablation mechanism occurred on low-index lattice planes of single crystal diamond - Yantao Gong; Juncheng Lei; Weiqing Li; Ding-shun She; Wen Yue; Young Shawn (Functional Diamond)
The speed of laser scanning significantly influences the temporal and energetic distribution of the interaction between the laser and the material, thereby impacting both the material removal rate and processing quality. For the purposes of improving the laser machining efficiency on the (100), (110), and (111) low-index lattice planes of single crystal diamond, laser ablation experiments have been carried out under the laser scanning speeds of 10, 20, 30, 40, and 50 mm/s. The effects of laser scanning speed on the depth, width, material removal rate (MRR) and surface morphology of the ablation microgrooves have been investigated to reveal ablation mechanism of single crystal diamond with anisotropy performances. The experimental findings indicate that a high laser scanning speed leads to the formation of narrow and shallow microgrooves with a rougher edge and a low material removal rate, owing to combined effects of oxidation and graphitization occurred on the low-index lattice planes of single crystal diamond. Compared with the (110) and (111) lattice planes, the microgrooves on the (100) lattice plane exhibit a greater width, a less depth, a low depth-to-width ratio and a higher material removal rate, attributed to the small atomic planar density, large interplanar spacing, and small binding energy between the adjacent crystal planes. As the laser scanning speed reduce to 20 mm/s, the material removal rate on the (100), (110), and (111) low-index lattice planes of single crystal diamond grow slowly, resulting from the progressively intensified plasma shielding effects during laser-material interaction.